2017
DOI: 10.1002/marc.201700399
|View full text |Cite
|
Sign up to set email alerts
|

Poly(vinylidene fluoride‐co‐chlorotrifluoroethylene) Modification via Organocatalyzed Atom Transfer Radical Polymerization

Abstract: To address the challenge of metal contamination, a "graft from" approach via organocatalyzed atom transfer radical polymerization (O-ATRP) is developed to synthesize poly(vinylidene fluoride-co-chlorotrifluoroethylene) (P(VDF-co-CTFE)) graft copolymers. N-phenylphenothiazine is utilized as a model organic photoredox catalyst for catalyzing the (co)polymerization of methyl methacrylate (MMA), methacrylate (MA), and n-butyl acrylate (BA). By employing this technique, high temporal control of polymerization and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 68 publications
0
15
0
Order By: Relevance
“…Our group developed a P(VDF-co-CTFE) gra modi cation strategy via O-ATRP by using N-phenylphenothiazine as the catalyst (Figure 3) [41]. A series of P(VDF-co-CTFE)-g-PMMA, P(VDF-co-CTFE)-g-PMA, and P(VDF-co-CTFE)-g-PBA were prepared under mild conditions with high temporal control.…”
Section: Phenothiazinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group developed a P(VDF-co-CTFE) gra modi cation strategy via O-ATRP by using N-phenylphenothiazine as the catalyst (Figure 3) [41]. A series of P(VDF-co-CTFE)-g-PMMA, P(VDF-co-CTFE)-g-PMA, and P(VDF-co-CTFE)-g-PBA were prepared under mild conditions with high temporal control.…”
Section: Phenothiazinesmentioning
confidence: 99%
“…Poly(vinylidene uoride-co-chlorotri uoroethylene) modi cation via organocatalyzed atom transfer radical polymerization. (Adapted with permission from Ref [41]…”
mentioning
confidence: 99%
“…Since the initial discovery in 2014, [71][72] series of organic photoredox catalysts (PCs) have been developed to mediate socalled organocatalyzed atom transfer radical polymerization (O-ATRP) or metal-free ATRP. [83][84][85][86][87][88][89][90][91] It offers a fascinating avenue to fabricate tailor-made polymers without metal residue. [92] Miyake and co-workers [93] firstly transferred O-ATRP from the batch reactor to the flow mode.…”
Section: Organocatalyzed Atom Transfer Radical Polymerization (O-atrp)mentioning
confidence: 99%
“…Despite their effectiveness, metal contamination limits their interest for biomedical and electronic applications. Significant effort has therefore been dedicated to develop photoredox metal-free ATRP (Chen et al, 2016 ; Pan et al, 2016b ; Hu et al, 2017 ; Ryan et al, 2017 ; Discekici et al, 2018 ). Pioneering work by Hawker's group demonstrated that 10-phenylphenothiazine (PTH) can be an effective organic photoredox catalyst for the polymerization of methacrylates under ultraviolet irradiation (Treat et al, 2014b ).…”
Section: Introductionmentioning
confidence: 99%